Pemberdayaan Bisnis melalui Adopsi Marketplace dan Penguatan Desain Kemasan dalam Upaya Peningkatan Pemasaran di Kelompok Tani Gula Semut Desa Kedungurang, Kabupaten Banyumas - Aufa Rizka Azzumi; Muhammad Ridwan; Ariq Cahya Wardhana; Nastiti Nur Indrayani; Fala Sifah Maharani; Windi Septiani; Jilly Ayu Puspita (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This ponder investigates the selection of computerized marketplaces and the fortifying of item bundling plan to upgrade the showcasing of palm sugar delivered by the Maju Makmur agriculturist bunch in Desa Kedungurang. Through a community-based approach, we given preparing and item advancement to progress item quality and grow advertise reach. Workshops on advanced promoting procedures and commonsense bundling plan driven to noteworthy deals development and financial advancement for the community. The selection of omni-channel e-commerce stages too encouraged more extensive advertise get to, expanding item perceivability and competitiveness. Modern item variations beneath the